Systematic generation of a once-through staged reactor design for direct methanation of biogas - Hillestad, Magne (Chemical engineering and processing, 2022)
With 40 mol% CO2, the energy content of biogas is too low to be used as motor fuel. Motor-grade compressed bio-methane can be produced by direct methanation of biogas with the use of hydrogen. A direct methanation process is considered here as the pre-processing step of separating the biogas is avoided. A systematic staging method is applied to design the process to upgrade biogas to motor-grade bio-methane by maximizing the production of methane with the use of the least possible reaction volume and subject to a quality specification. Here, a once-through process is the target so as to avoid the post-processing separation of the product and recycling. The most promising design is a three-stage configuration with water condensation after each stage. Shell and tube reactors are considered to be less expensive than micro-channel reactors. All three stages are placed in a single shell with boiling water on the shell side. The proposed design is verified by rigorous simulation. The method makes process intensification of chemical reaction systems possible, which is here demonstrated for direct methanation of biogas. •Systematic staging of direct methanation of biogas.•Maximizing the methane production with use of least possible reaction volume.•Once-through conversion of biogas to motor-grade fuel.•Intensified process with three stages in one reactor shell.